Knowledge on under-five childhood immunization schedule amongst parents at nurseries in Putrajaya and Cyberjaya in Malaysia - Mohd Zulkefli, Nor Afiah; Rusli, Mohammad Farhan; Juni, Muhamad Hanafiah (Mak Periodical Library, 2018)
Background: Knowledge on under-five childhood immunization has been identified as a key factor in determining understanding and compliance to the schedule. Understanding the current levels of knowledge and introducing a health intervention to improve the level will benefit the population to be healthier and reduce morbidity. Methods: A quasi-experimental study was conducted in nurseries in Putrajaya and Cyberjaya from January 2016 to January 2018. 98 respondents from Putrajaya were the intervention group and 98 from Cyberjaya were the wait-listed control group. The intervention was a technology based health education module. Intervention groups received the intervention through the messaging service of Whatsapp at pre-determined intervals. Respondents answered a validated, self-administered questionnaire at baseline, immediately post-intervention and 3 months post-intervention that were specifically targeted to examine their levels of knowledge. Results: Data was analyzed using Statistical Package for Social Science (SPSS) Version 23. The level of knowledge at baseline was 58.9% for the intervention group and 61.7% for the control group with no significant difference between both groups. At 3 months post-intervention the intervention group was 95.5% and the control was at 85.1%. Immediate post intervention showed a big gap between both groups. Conclusion: The level of knowledge improved after receiving the health intervention module and was effective in the increasing of knowledge among the respondents. However, there are still gaps in research that must be addressed in future studies to help further improve knowledge on under-five childhood immunization schedule.